IoT-Based Coin Slot of The Vending Machine - Kahar, Nani izzati; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2024)
This work introduces a comprehensive Internet of Things (IoT)-based system to revolutionize traditional vending machine operations. The focal points of this endeavor include the utilization of the Blynk Application for real-time notifications to service personnel, facilitating proactive maintenance and repair actions specific to coin slot issues. The hardware implementation will be orchestrated through an ESP32 microcontroller, augmented with GPS functionality, seamlessly integrated into the overarching IoT platform. This amalgamation aims to provide precise location tracking and enhance the overall monitoring capabilities of the vending machine. Moreover, the system employs an image and infrared sensor to identify and record objects within the coin slot, contributing to an intricate understanding of potential issues. This holistic approach seeks to elevate vending machine management, offering a paradigm shift towards intelligent, responsive, and efficient systems within the context of emerging IoT technologies.